2003
DOI: 10.1002/mawe.200300717
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diamond‐Like‐Carbon and Alumina‐Oxide articulating with Polyethylene in Total Hip Arthroplasty

Abstract: To reduce wear in joint bearings of total hip arthroplasty (THA) is the most important issue for improving long term results and implant survival. Due to low wear rates and excellent tribological features in simulator tests Diamond-Like-Carbon coating (DLC) of femoral balls is still discussed as an alternative articulation in THA. This clinical prospective study compares survivorship of DLCcoated femoral heads and of Aluminia-Oxide-(Al 2 O 3 ) heads articulating with Polyethylene (PE).Over a period of two year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 32 publications
0
68
1
2
Order By: Relevance
“…Indeed this has been identified as the main cause for implant failure in the explant study by Taeger et al, as observed in Fig. 5 [38]. Fracture and cracking was noted along the wear scars by Fisher et al [42], shown in Fig.…”
Section: Suggested Reasons For Coating Failure In In Vitro Testingmentioning
confidence: 82%
See 3 more Smart Citations
“…Indeed this has been identified as the main cause for implant failure in the explant study by Taeger et al, as observed in Fig. 5 [38]. Fracture and cracking was noted along the wear scars by Fisher et al [42], shown in Fig.…”
Section: Suggested Reasons For Coating Failure In In Vitro Testingmentioning
confidence: 82%
“…As the explant study (Taeger et al [38]) also suggests that the wear debris is the likely cause of premature biological failure, the main aim for improvement in the coatings is to make them more resistant to wear (resulting in less debris) or to make the debris less harmful to the body.…”
Section: Potential Reasons For Differing Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DLC deposition process can be tailored to produce a strong amorphous film with no grain boundaries and hardness values ranging from 10 to 80 GPa [33]. However, DLCcoated titanium alloy femoral heads failed in clinical use [47], and DLC-coated CoCr femoral heads reportedly do not reduce wear compared with uncoated CoCr heads in hip simulator tests [18], but the durability and wear performance of DLC-coated ceramic materials is unknown. DLC-coated Mg-PSZ reportedly forms a stronger construct than DLC-coated CoCr [35], suggesting an improved resistance to abrasive wear.…”
Section: Introductionmentioning
confidence: 99%